Work Life Balance and Working Women - Katait, Sanjay Keshaorao; Phule, Kishor (Journal of Commerce and Trade, 2018)
The present role of working women has changed worldwide due to economic conditions and social demands. Thishas resulted in to increase in tremendous pressure to develop a career against their malecounterparts while sustaining active engagement in personal life.The mounting work pressure is taking a toll on the workingwomen leaving them with less time for themselves. The increasingresponsibilities on the personal front with the technologicalblessings like mobile phones, notepads, etc. that keepswork life integrated with personal life and creates imbalances, stress onpersonal and professional fronts. Such imbalance has a negative effect on personal life of working women which in turn have taken form of social hazards such as increasing number of divorces, infertility due to high stress levels.Thisaffects the working women's physical, emotional and social well-being.Thus, achieving work life balance is a necessity for workingwomen to have a good quality of life. This research paper is an attempt toexplore the tough challenges faced by working women inmaintaining a balance between their personal and professionallife. Classification-JEL : B54, D63, E24